2017
DOI: 10.1038/s41598-017-02788-9
|View full text |Cite
|
Sign up to set email alerts
|

φBO1E, a newly discovered lytic bacteriophage targeting carbapenemase-producing Klebsiella pneumoniae of the pandemic Clonal Group 258 clade II lineage

Abstract: The pandemic dissemination of KPC carbapenemase-producing Klebsiella pneumoniae (KPC-KP) represents a major public health problem, given their extensive multidrug resistance profiles and primary role in causing healthcare-associated infections. This phenomenon has largely been contributed by strains of Clonal Group (CG) 258, mostly of clade II, which in some areas represent the majority of KPC-KP isolates. Here we have characterized a newly discovered lytic Podoviridae, named φBO1E, targeting KPC-KP strains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 42 publications
3
40
0
1
Order By: Relevance
“…The latent period time (18 min) of phage vB_KpnS_Kp13 was longer that of Klebsiella phage ϕBO1E (Podoviridae; 10 min) 35 . The burst size of vB_KpnS_Kp13 (~220 phage particles/infected cell) was not extremely high compared with two phages in the Siphoviridae 36 and Podoviridae 35 families, but they assured an effective bactericidal potential as vB_KpnS_Kp13 could prevent proliferation of its target bacterium from an MOI of 0.01. Compared to phage TSK1 21 , this value was lower by 2 orders of magnitude and therefore was more effective.…”
Section: Discussionmentioning
confidence: 91%
“…The latent period time (18 min) of phage vB_KpnS_Kp13 was longer that of Klebsiella phage ϕBO1E (Podoviridae; 10 min) 35 . The burst size of vB_KpnS_Kp13 (~220 phage particles/infected cell) was not extremely high compared with two phages in the Siphoviridae 36 and Podoviridae 35 families, but they assured an effective bactericidal potential as vB_KpnS_Kp13 could prevent proliferation of its target bacterium from an MOI of 0.01. Compared to phage TSK1 21 , this value was lower by 2 orders of magnitude and therefore was more effective.…”
Section: Discussionmentioning
confidence: 91%
“…pneumoniae specific bacteriophage TSK1 has the distinctive character to form opaque halo zone surrounding the clear zone of plaque. The hazy halo zones suggest the ability of TSK1 phage to produce soluble, polysaccharide-degrading enzymes 20 . Previous research showed that the formation of halo zones is an indicator for the presence of phage tail-associated exopolysaccharide (EPS) depolymerases 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic change in phage particles number during a replicative cycle was monitored to determine the latency period, the eclipse period and the burst size of vB_Kpn_F48 as previously described [ 28 ] with minor modifications. Briefly, the host strain 12C47 was grown in aerobic conditions at 37 °C to mid-exponential phase (OD 600 = 0.3–0.4, corresponding to ≈1–2 × 10 8 CFU/mL).…”
Section: Methodsmentioning
confidence: 99%